Integrated ISPH approach with artificial neural network for magnetic influences on double diffusion of a non-Newtonian NEPCM in a curvilinear cavity - Weaam Alhejaili; Munirah Alotaibi; Abdelraheem M. Aly (AIMS Mathematics)
The artificial neural network (ANN) in conjunction with the incompressible smoothed particle hydrodynamics (ISPH) approach, deals with exothermic reaction effects on Cattaneo-Christov (Ca-Ch) heat and mass transport of nano-enhanced phase change material (NEPCM) in a curvilinear cavity. The ANN model, trained on data obtained from ISPH simulations, accurately predicted the mean $ \overline{Nu} $ and $ \overline{Sh} $ values. Two cases of boundary conditions included $ \left(T_{h}&C_{h}\right) $ on top/bottom walls and $ \left(T_{c}&C_{c}\right) $ on vertical walls and inner ellipse for C1. The boundary walls of a curvilinear cavity were kept at $ \left(T_{h}&C_{h}\right) $ and the inner ellipse was maintained at $ \left(T_{c}&C_{c}\right) $ for C2. The pertinent parameters were scaled as Frank-Kamenetskii number $ Fk\left(0-1, \right) $ Ca–Ch heat, mass transfer parameters $ \left({δ }_{θ }&{δ }_{Φ }\right)(0-0.2), $ Hartmann number $ Ha(0-60), $ buoyancy ratio parameter $ N(-2-4) $, power law index parameter $ n(1.1-1.4) $, Rayleigh number $ Ra({10}^{3}-{10}^{5}) $, Soret/Dufour numbers $ \left(Sr&Du\right)(0-0.5) $, and fusion temperature $ {θ }_{f}(0.1-0.9) $. The simulation results demonstrated the effectiveness of Ca-Ch heat and mass transport parameters in lowering temperature and concentration within a curvilinear cavity at C1 and C2. Increasing $ {δ }_{θ }&{δ }_{Φ } $ from 0 to 0.2 resulted in a $ 44.1% $ and $ 48.9% $ drop in velocity field at C1 and C2, respectively. Boundary conditions (C1 and C2) significantly affected mass, heat transfer, heat capacity ratio, and velocity field within a curvilinear cavity. An increase in Power law index $ n $ from 1.1 to 1.4, reduced a velocity field by $ 64.68% $ and $ 64.66% $ at C1 and C2, respectively. Increasing $ Sr $ and $ Du $ helped distribute concentration. When $ Sr $ and $ Du $ were raised from 0 to 0.5, the velocity field increased by $ 34.17% $ and $ 29.73% $, respectively, at C1 and C2.